Study on anisotropic behavior of 7075 Al alloy after extrusion - Yi Zhang; Jin Ma; Qiang Wang; Yongbiao Yang; Mingjie Zhu; Penglai Jia; Yuhao Duan; Zhimin Zhang (Materials Research Express, 2022)
For an extrusion process of 7075 Al alloy, the extrusion direction of the initial blank is changed to study the mechanical properties of the formed plates and characterize their microstructure. The as-received bar is extruded 7075 Al alloy. The secondary extrusion deformation is along and perpendicular to the initial extrusion direction. The results show that the anisotropy of mechanical properties of the two samples decreases obviously after secondary deformation. The anisotropy of yield strength and ultimate tensile strength of ED90 sample is lower than that of ED0 sample, but the plastic anisotropy is slightly higher than that of ED0 sample. In addition, the recrystallized grain proportion of ED90 sample is high and the texture strength is low, so the Schmid factor in the three directions is similar. The tensile fracture mode of the two samples belongs to ductile fracture, but the morphology of dimple and the size of cleavage plane are slightly different.